2013
DOI: 10.1109/jqe.2013.2276122
|View full text |Cite
|
Sign up to set email alerts
|

All-Optical Stochastic Logic Gate Based on a VCSEL With Tunable Optical Injection

Abstract: Abstract-We study the dynamics of a vertical-cavity surfaceemitting laser with continuous-wave orthogonal optical injection from a tunable laser. We use the dynamical properties of polarization bistability and the interplay with internal or external noise to demonstrate numerically a reliable logic output to two logic inputs encoded in the optical frequency of the injected light. This all-optical configuration is more than ten times faster than the electro-optical implementation and has the advantage of operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…(1) and (20) are ignored in the following calculation, owing to the slight influence on the PS of VCSEL [23]. According to the related reports [14][15][16][17], the PS or logic output states of an optically injected VCSEL depends on some key parameters, such as the injection current of the M-VCSEL and the S-VCSEL, μ M and μ S , as well as optical injection strength k inj. As presented in [17], for any injection current μ M of the M-VCSEL, with the increase of the applied electric field, the polarization of the S-VCSEL with POI oscillates periodically when μ S = 1.2 and k inj = 10ns −1 (the same below).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(1) and (20) are ignored in the following calculation, owing to the slight influence on the PS of VCSEL [23]. According to the related reports [14][15][16][17], the PS or logic output states of an optically injected VCSEL depends on some key parameters, such as the injection current of the M-VCSEL and the S-VCSEL, μ M and μ S , as well as optical injection strength k inj. As presented in [17], for any injection current μ M of the M-VCSEL, with the increase of the applied electric field, the polarization of the S-VCSEL with POI oscillates periodically when μ S = 1.2 and k inj = 10ns −1 (the same below).…”
Section: Resultsmentioning
confidence: 99%
“…These phenomena are often considered as a drawback, degrading the laser performance. At present, they can also be generalized to apply some areas of great concern, such as polarization switch, polarization multiplexing and demultiplexing and optical logic gates devices [11][12][13][14][15][16][17]. It is a very attractive scheme that optical logic devices are designed by means of the PS of an optically injected VCSEL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We use the well-know spin-flip model [18] for a VCSEL operating in the fundamental transverse mode, extended as in [19] to account for external optical injection. The equations written in the frequency reference frame of the injected field are:…”
Section: Modelmentioning
confidence: 99%
“…Optical switching and bistability have attracted much attention due to their wide application prospects in optical memory, optical logic-gate, optical information processing, and so on [1][2][3][4][5][6][7]. Previous studies have demonstrated that semiconductor lasers (SLs) can exhibit diverse switching and bistability behaviors under different external pertur-bations [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%